Discrete-Time Asymptotic Tracking Control System for a Satellite with a Solar Panel - Emirsajłow, Zbigniew (Applied sciences, 2025)
The aim of this work is to develop a discrete-time control algorithm that allows the attitude angle of a satellite with an attached solar panel to track a prescribed periodically changing reference signal with zero asymptotic error. Using the concept of the general regulation theory for the state space setup, combined with a time discretization procedure based on the Cayley–Tustin transformation, we derive an error feedback controller. In our control analysis, we prove and explore several system-theoretic properties that are preserved under this continuous-to-discrete time transformation. The obtained discrete-time controller is then applied as a digital control system, demonstrating zero asymptotic tracking error. The theoretical results are tested on a numerical example and computations are performed within the MATLAB R2024b environment, confirming the highly useful nature of the developed approach. The controller also shows some robustness with respect to parametric uncertainty in the satellite model.